Implementation of E-invoicing System in Cambodian Context - Sok, Lykhun; Svatá, Vlasta, 1952-; Novák, Richard, 1973-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
The electronic invoicing system has been widely adopted in many nations throughout the world, and its implementation within a country's commercial sector is critical to the success of that sector. Developing nations, on the other hand, still need to play catch-up in terms of putting this idea into practice. During the course of this investigation, we are going to devise a solution for an electronic invoicing system that is appropriate for the context of Cambodia. This study was carried out by collecting quantitative data pertaining to the implementation of the e-invoicing system in ASEAN and European countries, conducting a review of relevant policies and documents written in both Cambodian and English languages, and conducting interviews with individuals who work in relevant organizations.
Vedoucí práce: Vlasta Svatá
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses